Automated Conveyor Belt Object Counting with Integrating Real-Time Monitoring Dashboard - NG, WEN KANG; Mohd Fadly Abd Razak, (Progress in Engineering Application and Technology, 2026)
The current work proposed in this research work is focused on design, implementation, and evaluation of an automated object counting technique on industrial conveyor belts using IR sensors coupled with the Arduino Mega 2560 microcontroller. The system solves several problems associated with manual counting which are usually monotonous, tiring, time-consuming and a safety concern to the workers. The counting process performed by the system enables accurate identification and immediate tracking of product quantities for enhanced stock control and product manufacturing. The approach involves implementation of an IR sensor for object detection and a microcontroller for the processing of data which is seen on the LCD in a live manner, at the same time, all data are tabulated on a monitoring dashboard. The language used in programming is based on the use of Arduino IDE software, to allow for scalability and ease of use. The suggested approach lowers the labor expenditure, avoids production stagnation, and maintains higher accuracy of items’ traceability. The proposed solution reduces labor dependency, enhances operational efficiency, and provides a cost-effective automation option suitable for small and medium-sized enterprises (SMEs).